Exploring Niosomes: A Comprehensive Review of their Structure, Formulation, and Biomedical Applications - Javaid, Sumiyya; Rana, Tayyaba; Naeem, Zainab; Sajid, Nayab (Currents in Pharmaceutical Research, 2024)
Niosomes are a novel class of non-ionic surfactant vesicles. They have emerged as promising vesicles for the delivery of a diverse range of therapeutic agents. Niosomes are implied for the improvement of stability and solubility of molecules used in pharmaceutical components. The current study delved into the formulation methods, applications, and recent advancements in niosomal technology. They offer various benefits over other drug delivery systems due to their biocompatibility, biodegradability, and versatility. The first section of this study outlined the background, detailed structure, and characteristics of niosomes. Niosomes are quite distinct in their characteristics as they have the ability to encapsulate both hydrophilic and lipophilic drugs. The second section of the current study highlighted various methods employed for niosome preparation, such as film hydration, reverse-phase evaporation, and microfluidic techniques. By modifying the lipid composition and surfactants, specific physicochemical properties, such as size, lamellarity, and surface charge can be achieved. The final section discussed applications of niosomes across pharmaceutical, cosmetic, and biotechnological fields. These include targeted drug delivery, gene delivery, cosmetic ingredient encapsulation, and vaccine adjuvant systems. Additionally, the recent advancements in niosome research have been discussed as well.